The mortality in traffic in Montenegro: the meaning of first aid in prevention of it. (1st March 2011) - Pejakovic, M; Pejakovic, V; Utjesinovic, J; Bogdanovic, M; Pavlicic, R; Tadic, N; Knezevic, V
Abstract : There are about 230 000 drivers in Montenegro. The most common reasons why the accidents happen are driving under the influence of alcohol, exhaustion, bad knowledge of the traffic rules and poor roads quality. The aim of study is to show the mortality on roads in Montenegro and to suggest prevention measures. Methods: Data about traffic accidents from 2004 to 2010 were collected and analysed from the Ministry of Internal Affairs Montenegro. Results: 12 913 persons were hurt in traffic accidents in Montenegro from 2004 to 2010. From that amount 524 (4%) were killed. Death rate = 14/100 000 persons. The drivers consist 46% (239) of cases of the total number of those killed. Co-drivers consist about 34% (177) and pedestrians consist about 20% of the cases (108). Death could be prevented in many cases in which people died before reaching a hospital. Basic first-aid training to groups, such as commercial vehicle drivers, who are most likely to be among the first at crash scenes, may be a more appropriate use of scarce resources. As the first step in these activities the authors have created a first aid reference book. Doctors will perform the education with the help of the Red cross and similar organisations and provide knowledge to these active in traffic. Conclusion: Tertiary measures of prevention bring to the decrease of mortality as well as to the weakening of the effects of the injuries in traffic.